2020
DOI: 10.1002/jlb.3ru0420-668rr
|View full text |Cite
|
Sign up to set email alerts
|

HLA-DR-expressing NK cells: Effective killers suspected for antigen presentation

Abstract: HLA-DR-expressing cells comprise an intriguing group of NK cells, which combine phenotypic characteristics of both NK cells and dendritic cells. These cells can be found in humans and mice; they are present in blood and tissues in healthy conditions and can expand in a spectrum of pathologies. HLA-DR + NK cells are functionally active: they produce proinflammatory cytokines, degranulate, and easily proliferate in response to stimuli. Additionally, HLA-DR + NK cells seem able to take in and then present certain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 68 publications
1
40
0
2
Order By: Relevance
“…In this work, we have revealed that HLA-DR-positive cells are also expanded among CD56 bright CD3 − and CD56 + CD3 + subsets in the peripheral blood of the individuals primarily infected with lung tuberculosis ( Figure 1A ). Considering the reduced content of CD3 + CD56 − T cells and CD3 − CD56 − HLA-DR + cells observed by us in these patients, HLA-DR + NK cells, which often display activated phenotype and functions both in normal conditions and during pathology ( 36 ), may compensate for certain deficiencies of the adaptive anti-mycobacterial response.…”
Section: Discussionmentioning
confidence: 86%
“…In this work, we have revealed that HLA-DR-positive cells are also expanded among CD56 bright CD3 − and CD56 + CD3 + subsets in the peripheral blood of the individuals primarily infected with lung tuberculosis ( Figure 1A ). Considering the reduced content of CD3 + CD56 − T cells and CD3 − CD56 − HLA-DR + cells observed by us in these patients, HLA-DR + NK cells, which often display activated phenotype and functions both in normal conditions and during pathology ( 36 ), may compensate for certain deficiencies of the adaptive anti-mycobacterial response.…”
Section: Discussionmentioning
confidence: 86%
“…Fourth, GO analysis for NK cells showed the enrichment of antigen processing and presentation of peptide antigen via MHC II, which needs to be interpreted carefully. NK cells are not professional antigen-presenting cells (APCs), and they are important members of the innate immune system to directly eliminate virus-infected cells and tumor cells through their natural cytotoxic capacity without prior priming ( 44 ). Genes enriched for antigen processing and presentation mainly included human leukocyte antigen (HLA) -DPB1, HLA-DPA1, HLA-DQA1, HLA-DRB1, and HLA-DRB5, all these enriched genes are classical HLA II molecules.…”
Section: Discussionmentioning
confidence: 99%
“…Genes enriched for antigen processing and presentation mainly included human leukocyte antigen (HLA) -DPB1, HLA-DPA1, HLA-DQA1, HLA-DRB1, and HLA-DRB5, all these enriched genes are classical HLA II molecules. HLA-DR-expressing NK cells have been reported to be detected in the blood and tissues in healthy individuals, and their functions are associated with enhanced production of proinflammatory cytokines, degranulation, and proliferation upon stimuli ( 44 ). In vitro , HLA-DR-expressing NK cells pre-activated with cytokines have been reported to induce nonspecific activation and partial differentiation of CD4 T cells in previous publications ( 45 , 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, we observed an increase of HLA-DR expression on NK cells in the Hyper subgroup as compared to the Hypo subgroup. HLA-DR + NK cells have been associated with a less mature phenotype with antigen-presentation ability (41,42). This might explain the overall hyper-responsiveness as seen in the Hyper subgroup where NKs, in addition to professional antigenpresenting cells such as DCs, leads to further activation of Tcells.…”
Section: Discussionmentioning
confidence: 99%